Ensuring effective and sustainable radionuclide delivery and its impact on the development of nuclear medicine in the developing world with special reference to Nigeria - Orunmuyi, T. Akintunde; Sathekge, M. Mike; Buscombe, R. John (World Journal of Nuclear Medicine, 2019)
Recent activities of Boko Haram, a local extremist group in Nigeria, raise concerns about a nuclear terrorist attack. Whereas nuclear medicine (NM) relies on the timely delivery of radioactive sources, a robust security structure that assures public safety is the backbone for its beneficial use. NM radionuclides have short half-lives and carry an insignificant risk for acts of terrorism. Yet, their importation and delivery in Nigeria receive undue scrutiny in a bid to implement a strict nuclear security regime. These actions prevent timely delivery of radionuclides with direct consequences on quality and economic viability of nuclear medicine. There have been no accounts of terrorist acts accomplished with NM radionuclides. Thus, it is important the NM community question the current approach that has contributed to the loss of NM services in Nigeria and proposes a more logical strategy for securing their supply. We also highlight the need for developing local pragmatic solutions when implementing global recommendations in developing countries.
Keywords: Development; nuclear medicine; nuclear safety